Hereditary sensory radicular neuropathy (HSN) - Yalaz, Kalbiye; Renda, Yavuz; Kuru, Bekir (The Turkish Journal of Pediatrics, 1980)
A case of autosomal recessive hereditary sensory neuropathy (HSN Type II), with an onset at the end of the first decade of life is presented. Family history revealed that the parents were first cousins and the patient’s brother who had had similar clinical findings had died at the age of 20 years from an unknown disease. The symptoms of which had been impaired pain sensation resulting in repeated injuries, ulceration, painless bone fractures, mutilating arthropathies, and acroosteolysis. On the basis of the clinical course and the laboratory investigation of the present case it can be said that in autosomal recessive hereditary sensory neuropathy type II, progressive as well as non-progressive types exist.